Faktor-Faktor Yang Mempengaruhi Permintaan dan Penawaran Cabe Merah - Nista Zamili; Gustami Harahap; Rahma Sari Siregar (Jurnal Ilmiah Pertanian ( JIPERTA), 2020)
This research aims to know what are the factors that influence the demand and supply of red pepper in MMTC market Medan Medan Estate sub district percut sei tuan deli serdang district. This research was carried out in July 2017. This research using sampling method with way of census and purposive sampling, in this research sam 20 for trader and sample for consumer 40. Sample in this research is merchant selling red chilli and consumer shopping red chilli in MMTC highway market Medan in village medan estate sub district percut sei host district deli serdang. Simultaneously consumer opinion has a significant influence in this case because if the opinion of red chili consumers is high it can affect the demand because the size of the opinion will be able to affect the demand for goods tersebuat.. Factors affecting the supplyple used is of red chili in Pasar Raya MMTC Medan simultaneously have a positive effect is the purchase price of red pepper, production cost, profit. Partially production cost give significant influence to red chilli supply in Pasar Raya MMTC Medan.